“Ain’t She a Bute?”: The Importance of Proper History Taking in a Case of Inappropriate Use of Horse NSAID in a Human - Sawalha, Khalid (Clin Pract, 2021)
A 41-year-old woman with no significant past medical history presented to the hospital with complaints of nausea, vomiting, and generalized weakness over two weeks. The patient did not seek medical attention as she assumed that her symptoms willwould resolve. Following her initial denial of drug abuse and her abnormal urine drug screening, we discussed the findings with the patient. She later admitted to using both amphetamines and marijuana. This led us to take a detailed social history that revealed an unexpected event.